Determinant of Smoking Behavior in Students at the Health Sciences Faculty of Universitas Muhammadiyah Pontianak - Mutya Melinda; Alya Putri Maharani; Pitri Lestari; Linda Suwarni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Risk data for 2018 showed an increase in the number of smokers in the Indonesian population, with 33.8% of those over 15 years of age being predominantly male (62.9%). The increase in this number was followed by a rise in some smoking-related diseases such as hypertension, stroke, and other chronic diseases. There are many factors that affect smoking behavior.. Objective: The study aimed to find out the prevalence of smoking behavior in students as well as the determinants with smoke behaviour in students at the Health Sciences Faculty of Universitas Muhammadiyah Pontianak. Method: The research uses quantitative research as well as observational analytical design with a cross sectional approach. The sample of this research was partly male students at the Faculty of Health Sciences a total of 64 with incidental sampling techniques. Data analysis using unvariate and bivariate analysis (uji Chi-Square). Result: This study showed that there was a significant correlation between the role of parents, the influence of peers, the impact of advertising and smoking behavior on students of Universitas Muhammadiyah Pontianak (p value < 0.05) with the prevalence of students who smoke 45.3%. Conclusion: Continuous health promotion and implementation of the No Smoking Area (KTR) in the campus environment are needed.